INDIAN CORPORATE FINANCIAL REPORTING SYSTEM: A STUDY ON THE CASH FLOWS OF SELECTED PRIVATE ENTERPRISES - Kumar Das, Santanu (International Journal of Research -GRANTHAALAYAH, 2016)
Corporate financial reporting plays an important role in growing phenomenon of Privatization. The present study is based on the reports of Private Enterprises for three years. Findings revealed that the companies were presenting their annual reports. A privately owned enterprise refers to a commercial enterprise that is owned by private investors, shareholders or owners. The recent trend in financial reporting includes presentation and discloser of accounting aspect, corporate governance, corporate social responsibility and narrative reporting. The present paper will examine the cash flow statements of Maharastra Scooters Ltd., Tata Chemicals Ltd. and TVS Srichakra. In corporate financial reporting cash flow statement tells us the net cash flow activities, particularly its operating, investing and financial activities. These indications are helpful to analyze cash flow. This explains the sources and applications of liquidity of company. Keeping the importance of financial reporting in modern world the present paper attempts to analyzed and evaluate the financial reporting system in some selected units of private enterprises in India.